THE EFFECT OF THE DISTRIBUTION OF SEA SURFACE TEMPERATURE IN THE INDIAN OCEAN SOUTH OF JAVA ON THE CATCH OF YELLOWFIN TUNA (Thunnus albacares) USING AQUA MODIS SATELLITE IMAGERY - Putra, Yudha Erlangga; Syarifuddin, Hutwan; Sumadja, Wiwaha Anas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Tuna (Thunnus sp.) is the second largest foreign exchange earner after shrimp. One type of tuna which is an export commodity is yellowfin tuna (Thunnus albacares). Research on the effect of the distribution of sea surface temperature in the Indian Ocean south of Java on the catch of yellowfin tuna (Thunnus albacares) has been carried out at the Nizam Zachman Ocean Fishery Port (PPS) from April 8 to April 30, 2021. This study aims to determine the effect of sea surface temperature (SST) on the catch of yellowfin tuna. The research method used was the method of observation and analysis of satellite imagery. Coordinate data and the number of catches were obtained from the Ocean Fishery Port Logbook (PPS) Nizam Zachman. SPL data obtained from satellite imagery Modis Aqua Level 3. The data was obtained and then analyzed using a simple regression test and the F test results of regression analysis showed that the correlation coefficient (R) of 12.7% and the coefficient of determination (R2) of 1,6% means that 1.6% of yellowfin tuna catches are influenced by SST and 98.4% is influenced by other factors. The F test results show that the SPL significance value is 0.332. The conclusion is that changes in SST have no significant effect on the catch of yellowfin tuna.